Investment feasibility study of implementing electric conversion motorcycle in Indonesia: A sustainable development perspective - Imansuri, Febriza; Wirandi, Mohammad; Sumasto, Fredy; Aisyah, Siti; Permana, Al Kautsar (Universitas Sultan Ageng Tirtayasa, 2023)
The cause of global warming occurring in the world originates from the transportation sector, particularly Internal Combustion Engine (ICE) vehicles using fossil fuels. As a response, the Indonesian government has enacted regulations aimed at accelerating the adoption of electric vehicles. Electric vehicles developed in Indonesia encompass two-wheeled, three-wheeled, four-wheeled, and other types that operate by utilizing electrical energy stored in the vehicle's battery. One notable development involves the conversion of ICE motorcycles into electric motorcycles. This study seeks to assess the investment feasibility of implementing convertible motorcycles from economic, environmental, and social perspectives. The economic aspects are evaluated by calculating net present value (NPV) and payback period (PP), with the study's results demonstrating the economic viability of implementing convertible motorcycles. Furthermore, environmental considerations involve the comparison of chemical substances emitted as pollutants, with the results indicating the feasibility of this approach due to its potential to reduce air pollution. Lastly, the social aspect encompasses the review of potential impacts should converted electric motorcycles be produced on a large scale. The success of implementing convertible motorcycles necessitates the collaboration of various stakeholders, including the government, small and medium enterprises, electricity service providers, and the awareness of the public.